Wednesday

April 23, 2014

April 23, 2014

Posted by **Peter** on Friday, October 28, 2011 at 1:05am.

- Algebra 2 -
**Steve**, Friday, October 28, 2011 at 11:27amAs you know from the Remainder Theorem, dividing p(x) by (x-a) gives f(a) as the remainder.

we have f(-2) = 7

f(-2) = 4 + 6 + 2k = 7

2k = -3

k = -3/2

So, we have x^2 - 3k - 3

**Related Questions**

algebra - i need help with this problem. much appreciated. 2k^3+ 7k^2+1k+7 ...

maths - Let ( x(square)+ 3x +1) over (2 x(square) -5x+2) = k ----------be y 1) ...

Algebra - Can someone help me, I am stuck and do not know how to complete. Maybe...

POLYNOMIALS - ok, this might be a bit torturous, but if anyone is patient enough...

7th grade pre algebra - We need assistance solving 3 + 2(k+1) = 6 + 3k I know ...

grade 9 math - Does this answer seem correct. 2k+3=4k-5 2k-4k+3-3=-5-3 2k-4k=-5-...

help,math - simplify (x+2)/(x) divided by (x-2)/(3x) (x+2)/(x) divided by (x-2)/...

Pre-algebra - I have some practice problems, and I need to have them worked out...

Pre-algebra - I have some practice problems, and I need to have them worked out...

intro cal - the first 3 term of a geometric progression are k-4, 2k-4, 4k+4. ...